Independent association of weight-adjusted waist index with asthma in U.S. adolescents: Mediating roles of eosinophil percentage, total cholesterol, and HDL cholesterol - Lei He; Yingxia Deng; Xiaohua Liu; Yao Wang; Jing Tang (PLoS ONE, 2025)
Background Obesity is a risk factor for asthma in adolescents. “Although body mass index (BMI) is the most widely used metric for assessing obesity, it has several limitations. The weight-adjusted waist index (WWI) is a novel central obesity indicator and accurately reflects body composition. We aimed to explore the association of WWI with asthma in adolescents using NHANES 1999–2020 data. Methods WWI was calculated based on waist circumference (cm) divided by the square root of weight (kg). Current asthma status in adolescents was determined based on participants’ self-reports. Multivariate logistic regression analysis, restricted cubic spline (RCS) analysis, mediation analysis, and stratified analysis were used to comprehensively explore this association. Results A total of 15,796 adolescents were included. In the fully adjusted model, WWI was positively associated with current asthma in adolescents (odds ratio 1.252, 95% confidence interval 1.125–1.392, p = 0.0001). Participants in the highest WWI quartile (Q4) showed a 54.5% higher prevalence of asthma compared to Q1 (p for trend = 0.0007).. RCS modeling indicated that the association was linear. Mediation analyses indicated that blood eosinophil percentage (EOS%), total cholesterol (TC), and high-density lipoprotein cholesterol (HDL-C) partially mediated this association by 9.89% (p < 0.0001), 7.47% (p = 0.048), and 8.24% (p = 0.044), respectively. This association was independent of BMI, and BMI also did not significantly interact with this association (p for interaction = 0.682). Conclusions WWI was linearly and positively associated with the prevalence of current asthma among U.S. adolescents, independently of BMI. EOS%, TC, and HDL-C partially mediated this association.